Macleaya cordata isoquinoline alkaloids attenuate Escherichia coli lipopolysaccharide-induced intestinal epithelium injury in broiler chickens by co-regulating the TLR4/MyD88/NF-κB and Nrf2 signaling pathways - Liu, Yang; Han, Kai; Liu, Hua; Jia, Gang; Comer, Luke; Wang, Guanlin; Pan, Zizhu; Zhao, Yiqian; Jiang, Shuzhen; Jiao, Ning; Huang, Libo; Yang, Weiren; et al. (Frontiers in Immunology, 2024)
This study sought to explore the effects and potential mechanisms of dietary supplementation with isoquinoline alkaloids (IA) from Macleaya cordata to alleviate lipopolysaccharide (LPS)-induced intestinal epithelium injury in broilers. A total of 486 1-day-old broilers were assigned at random to a control (CON) group, LPS group, and LPS+IA group in a 21-d study. The CON and LPS groups received a basal diet, while the LPS+IA group received a basal diet supplemented with 0.6 mg/kg IA. At 17, 19, and 21 days of age, the LPS and LPS+BP groups were injected intraperitoneally with LPS, and the CON group was intraperitoneally injected equivalent amount of saline solution. The results manifested that LPS injection caused intestinal inflammation and lipid peroxidation, disrupted intestinal barrier and function, and increased the abundance of harmful microorganisms. However, dietary IA supplementation alleviated LPS-induced adverse changes in intestinal morphology, apoptosis, mucosal barrier integrity, cecum microorganisms, and homeostasis disorder by decreasing inflammatory cytokines and enhancing antioxidant-related genes expressions; inhibited LPS-induced increases in TLR4 and NF-κB expressions and decreases in Nrf2 and GPX1 genes expressions. Our findings indicated that Macleaya cordata IA addition attenuated LPS-induced intestinal epithelium injury and disorder of intestinal homeostasis by enhancing the anti-inflammatory and antioxidant capacity of broiler chickens possibly via co-regulating TLR4/MyD88/NF-κB and Nrf2 signaling pathways.